The role of strangeness in heavy-quark hadronisation from small to large collision systems with ALICE - Faggin Mattia (EPJ Web of Conferences)
Production measurements of strange hadrons originating from the hadronisation of charm quarks (prompt) and from beauty-hadron decays (nonprompt) offer a unique tool to study the heavy-quark hadronisation across different collision systems. This contribution discusses the final results of the ALICE Collaboration obtained by measuring strange D mesons in pp, p–Pb, and Pb–Pb collisions collected during the LHC Run 2. The first measurement of the production of orbitally excited charm-strange mesons in pp collisions is also reported. Additionally, the production measurements of prompt Ds+ mesons are compared to those of non-strange mesons across the different collision systems, along with the measurement of non-prompt Ds+ mesons in heavy-ion collisions. Lastly, the first studies of strange and non-strange D mesons using the large data sample of pp collisions at √s = 13.6 TeV harvested from the start of LHC Run 3 are presented.